RND-type Drug Efflux Pumps from Gram-negative bacteria: Molecular Mechanism and Inhibition - Venter, Henrietta; Mowla, Rumana; Ohene-Agyei, Thelma; Ma, Shutao (Frontiers in Microbiology, 2015)
Drug efflux protein complexes confer multidrug resistance on bacteria by transporting a wide spectrum of structurally diverse antibiotics. Moreover, organisms can only acquire resistance in the presence of an active efflux pump. The substrate range of drug efflux pumps is not limited to antibiotics, but it also includes toxins, dyes, detergents, lipids and molecules involved in quorum sensing; hence efflux pumps are also associated with virulence and biofilm formation. Inhibitors of efflux pumps are therefore attractive compounds to reverse multidrug resistance and to prevent the development of resistance in clinically relevant bacterial pathogens. Recent successes on the structure determination and functional analysis of the AcrB and MexB components of the AcrAB-TolC and MexAB-OprM drug efflux systems as well as the structure of the fully assembled, functional triparted AcrAB-TolC complex significantly contributed to our understanding of the mechanism of substrate transport and the options for inhibition of efflux. These data, combined with the well-developed methodologies for measuring efflux pump inhibition, could allow the rational design and subsequent experimental verification of potential efflux pump inhibitors. In this review we will explore how the available biochemical and structural information can be translated into the discovery and development of new compounds that could reverse drug resistance in Gram-negative pathogens. The current literature on efflux pump inhibitors will also be analysed and the reasons why no compounds have yet progressed into clinical use will be explored.